Application of the transgender male voice questionnaire in a Brazilian population sample - Schwarz, Karine; Villas-Bôas, Anna Paula; Cielo, Carla Aparecida; da Silva, Dhiordan Carodoso; da Silva, Eliane Dias; Fighera, Tayane Muniz; Costa, Angelo Brandelli; Lobato, Maria Inês Rodrigues; Spritzer, Poli Mara (Frontiers in Public Health, 2024)
ObjectivesThe aim of this study was to adapt and apply the Portuguese version of the Transgender Man Voice Questionnaire in a sample of Brazilian transgender men and to investigate the relationship between voice satisfaction and hormone therapy duration. In addition, we suggest reducing and reformulating the questionnaire for screening.MethodsWe conducted a cross-sectional study of 31 transgender men aged 18–50 years undergoing hormone therapy who answered a questionnaire adapted from the Transgender Woman Voice Questionnaire, validated in Portuguese. Sociodemographic and clinical data were collected from the individuals’ electronic medical records: age, smoking status, and type and duration of hormone therapy. The questionnaire, consisting of 30 questions rated on a Likert scale, was answered individually during a psychotherapy session. In each question, the gender-specific words were modified. Furthermore, we added a question: 31 (After GAHT, my voice became completely male), with the response options yes or no. In questions 32 and 33, asking participants to provide an overall rating of their voice. Total score ranged from 0 to 120, with higher scores indicating greater dissatisfaction with voice.ResultsMean patient age was 30.13 ± 7.6 years, and 19.4% were smokers. The mean duration of hormone therapy was 29.7 ± 24.9 months, and 95% received intramuscular testosterone cypionate, maintaining serum testosterone levels within the male reference range. The questionnaire mean total score was 51 ± 17.72. There was a significant negative correlation between the questionnaire total score and duration of hormone therapy (r = −0.484, p = 0.006). The questionnaire had a high level of internal consistency/reliability, with a Cronbach’s alpha coefficient of 0.95 for all items and a split-half Spearman-Brown coefficient of 0.96. For the elaboration of a screening tool, it is suggested to remove questions 8, 10, 12, 13, 14, 17, 19, 23, 27, and 29 and modify question 1.ConclusionLonger hormone therapy favors voice deepening and satisfaction with voice. The psychometric properties of the Transgender Man Voice Questionnaire are reliable, supporting its use as a screening tool in clinical practice and as an adjunct to the planning of vocal and communication support for transgender individuals.